Bridging Household Income Gap: Malaysia - Mohammad Zuhairie Zainudin; Ong Hway-Boon; Chong Choy-Yoke (Journal of International Business, Economics and Entrepreneurship, 2021)
The purpose of this paper is to examine the long run and the short run relationship between household income gap, physical capital, human capital, and technological progress in Malaysia. Based on the Solow's growth model, this study applied the panel cointegration estimation of the full modified ordinary least square (FMOLS), as well as the Granger causality analysis. The result showed that there is a short run and long run relationship running from physical capital, human capital, technological progress towards the income gap of M40 and B40 groups of households. This study is unique because it addresses the income gap between a group of households of the bottom 40% and middle 40% across all states in Malaysia.